Analisis Semiotika Properti Bali pada Latar Gim Pamali : The Hungry Witch - Onni Angelica Rheinilan Rheinilan; Intan Rizky Mutiaz; Dianing Ratri (KK Komunikasi Visual & Multimedia Fakultas Seni Rupa dan Desain Institut Teknologi Bandung, 2025)
Games are in demand by various groups in today's technological age. One of them is Pamali, an Indonesian horror game made by Storytale Studio. The object to be discussed is Pamali: The Hungry Witch series with a Balinese theme. The analysis in this study focuses on the visual of Balinese properties in the setting of the game which are part of the visual element. Visual elements are the most influential elements in connecting players with the game. The main focus is the visual of Balinese properties in the setting of the game. The purpose of this study is to assess whether the relationship between denotative signs and connotative visual of the properties in the setting in the game Pamali: The Hungry Witch is related or not to myths or culture in Bali. The Balinese properties in the setting are examined using Roland Barthes's semiotic approach. This study uses a qualitative descriptive analysis method. The results of the study reveal that there is a relationship between the relation of signs on the properties in the game setting with myths or culture in Bali. Myths in the game are reinforced by myths in Bali, bringing the game's setting closer to reality. Keywords: Visual of the Properties, Denotative, Connotative, Myth, Bali